Self-concept, social support, and subjective well-being of stay-at-home fathers from San Joaquin and Miagao, Iloilo. - Barreto, Ann Margarette; Sinaon, Arianne Krystelle (2011.)
This study on stay-at-home fathers was undertaken due to role reversal brought about by female labor migration. Given that males have taken on relatively new roles as full time parent to their children due to the migration of their wives, changes on their self-concept, the social support that they received, and their levels of subjective well-being were investigated. Ten stay-at-home fathers from the towns of San Joaquin and Miag-ao in southern Iloilo served as participants of this qualitative study. The respondents' ages from 27-56 years old. All of the respondents have children, and their wives have been working abroad for not less than a year. The results of the study show that stay-at-home have high levels of subjective weel-being as a result of them having a positive self-concept and available social support from friends, immediate family members, and relatives. The results of this study can serve as basis in establishing effective programs that will provide support for stay-at-home fathers.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Fathers